2010
DOI: 10.1097/mcg.0b013e3181c2987e
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-blind, Phase 3 Study of Fospropofol Disodium for Sedation During Colonoscopy

Abstract: The fospropofol 6.5-mg/kg dosing regimen was well tolerated and effective for sedation during colonoscopy and was associated with higher rates of sedation success, memory retention, and physician satisfaction than the fospropofol 2-mg/kg dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 13 publications
0
30
0
1
Order By: Relevance
“…COHEN and co-workers [76,77] conducted two randomised controlled trials of fospropofol or midazolam following premedication with fentanyl for colonoscopy and found that a dose of 6.5 mg?kg -1 provided appropriate sedation and high patient satisfaction. SILVESTRI et al [6] conducted a phase III randomised controlled trial of fospropofol 2 mg?kg -1 and 6.5 mg?kg -1 (those .65 years of age or with ASA category 3 or 4 had the dose reduced by 25%) .…”
Section: Emerging Pharmacological Sedatives In Bronchoscopy Fospropofolmentioning
confidence: 99%
See 1 more Smart Citation
“…COHEN and co-workers [76,77] conducted two randomised controlled trials of fospropofol or midazolam following premedication with fentanyl for colonoscopy and found that a dose of 6.5 mg?kg -1 provided appropriate sedation and high patient satisfaction. SILVESTRI et al [6] conducted a phase III randomised controlled trial of fospropofol 2 mg?kg -1 and 6.5 mg?kg -1 (those .65 years of age or with ASA category 3 or 4 had the dose reduced by 25%) .…”
Section: Emerging Pharmacological Sedatives In Bronchoscopy Fospropofolmentioning
confidence: 99%
“…Blood levels of propofol after administration of fospropofol reach lower peak levels and are more sustained than after administration of intravenous propofol leading to predictable levels of moderate sedation [74]. The advantage of its use is that it does not cause pain on injection, does not have the high risk of bacterial contamination seen with propofol and leads to predictable levels of sedation, however, it has the disadvantage that if a patient is over sedated they will require ventilatory support for longer and is associated with the commonly reported adverse effects paraesthesiae and pruritus [75,76].…”
Section: Emerging Pharmacological Sedatives In Bronchoscopy Fospropofolmentioning
confidence: 99%
“…8 Researchers have demonstrated higher rates of sedation success, less need for supplemental pain medication during sedation, and increased patient and physician satisfaction. [8][9][10][11] Sedation success rates of 87 to 89% for fospropofol have been cited, versus approximately 69% for midazolam. 5,9 Patient satisfaction was found to be 92.3% with fospropofol compared to 69.2% with midazolam, and physician satisfaction was almost 3 times higher with fospropofol.…”
mentioning
confidence: 99%
“…[8][9][10][11] Sedation success rates of 87 to 89% for fospropofol have been cited, versus approximately 69% for midazolam. 5,9 Patient satisfaction was found to be 92.3% with fospropofol compared to 69.2% with midazolam, and physician satisfaction was almost 3 times higher with fospropofol. 5,9 To date, published studies have focused on comparing the 2 sedative agents during either colonoscopy or bronchoscopy procedures; the use of such drugs in dentistry has yet to be studied.…”
mentioning
confidence: 99%
“…Phase II and III clinical trials showed faster recovery and greater patient satisfaction after sedation with fospropofol in comparison with midazolam. 27 Fospropofol causes less pain on injection than propofol, but is associated with a greater incidence of perineal paresthesia or pain. Fospropofol disodium has been approved by the US Food and Drug Administration for monitored anesthesia care in adults.…”
Section: Novel Propofol Derivativementioning
confidence: 99%